2020
DOI: 10.1371/journal.pone.0225939
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prediction of intraoperative and postoperative cardiac arrest requiring cardiopulmonary resuscitation and 30-day mortality in non-cardiac surgical patients

Abstract: Background The incidence, prediction and mortality outcomes of intraoperative and postoperative cardiac arrest requiring cardiopulmonary resuscitation (CPR) in surgical patients are under investigated and have not been studied concurrently in a single study. Methods A retrospective cohort study was conducted using the American College of Surgeons National Surgical Quality Improvement Program data between 2008 and 2012. Firth's penalized logistic regression was used to study the incidence and identify risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
35
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 14 publications
10
35
1
4
Order By: Relevance
“…Comorbid conditions are potentially major contributors to the ongoing high rates of intra‐operative cardiac arrest in low‐HDI countries over time. As described in our review and in other studies, a poor ASA physical status (3–5) is an important predictor of intra‐operative and anaesthesia‐related cardiac arrest events [3, 27–30]. Thus, the pre‐anaesthetic management of comorbidities plays a major role in minimising intra‐operative complications and adverse effects [26, 31–34].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Comorbid conditions are potentially major contributors to the ongoing high rates of intra‐operative cardiac arrest in low‐HDI countries over time. As described in our review and in other studies, a poor ASA physical status (3–5) is an important predictor of intra‐operative and anaesthesia‐related cardiac arrest events [3, 27–30]. Thus, the pre‐anaesthetic management of comorbidities plays a major role in minimising intra‐operative complications and adverse effects [26, 31–34].…”
Section: Discussionmentioning
confidence: 55%
“…The presence of SIRS/sepsis has been associated with high mortality rates [36, 37]. A recent study in a high‐HDI country revealed that baseline ASA 4–5 physical status and SIRS/sepsis were the most important risk‐factors for intra‐operative cardiac arrest and death [3]. The rate of peri‐operative cardiac arrest related to SIRS/sepsis is five‐fold higher in low‐HDI countries than in high‐HDI countries [26, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Starke Prädiktoren für den intraoperativen Kreislaufstillstand (IOCA) sind eine höhere Klassifikation der American Society of Anesthesiologists (ASA), akute Sepsis, Notfall‑/Akutfall, Anästhesietechnik und Alter [ 395 , 398 ]. Darüber hinaus gibt es verschiedene Faktoren wie Hypoxie, akuter Blutverlust mit Schock, Lungenembolie, Myokardinfarkt, Arrhythmie oder Elektrolytstörungen, die Ursache für einen intraoperativen Kreislaufstillstand sein oder dazu beitragen können [ 395 , 399 , 400 ].…”
Section: Evidenz Die In Die Leitlinien Einfließtunclassified
“…Although PERIOPCA is usually witnessed, with onset under monitoring in face of healthcare professionals and immediate availability of therapeutic means, aggressive cardiopulmonary resuscitation (CPR) does not always lead to return of spontaneous circulation (ROSC) and optimal long-term outcomes, with 55% of the survivors having poor neurological status [6,7]. The precipitating causes of PERIOPCA are usually known, but these patients constitute an heterogeneous group and their management often requires modification of traditional CPR algorithms [8]. The heterogeneous nature of PERI-OPCA is further demonstrated by the differences in survival between intraoperative and postoperative CPR [8].…”
Section: Introductionmentioning
confidence: 99%
“…The precipitating causes of PERIOPCA are usually known, but these patients constitute an heterogeneous group and their management often requires modification of traditional CPR algorithms [8]. The heterogeneous nature of PERI-OPCA is further demonstrated by the differences in survival between intraoperative and postoperative CPR [8]. Indeed, coagulation and hemostasis disturbances may be a perceived as a potential barrier to controlled hypothermia.…”
Section: Introductionmentioning
confidence: 99%